2003
DOI: 10.1002/jssc.200390000
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a quantitative assay using GC/MS for trace determination of free and conjugated estrogens in environmental water samples

Abstract: Validation of a quantitative assay using GC/MS for trace determination of free and conjugated estrogens in environmental water samples It has been shown that sewage effluent can discharge human hormones and pharmaceuticals, particularly estrogens and synthetic chemicals, which are able to disrupt animal and human endocrine systems into surface waters. Since many surface waters receive sewage effluent and are subsequently used to produce drinking water, it is of principal interest to assess their contamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 38 publications
1
17
1
Order By: Relevance
“…Recoveries for SPE-LC/MS/MS of pesticides in tap and river water observed a matrix related recovery [40] . In another study, no matrix influence was observed on method recoveries when assessed using deionised water and effluent [41] . This study also analysed influent for steroid levels, though no reference is made to method recoveries obtained using this matrix.…”
Section: Sample Preparationmentioning
confidence: 94%
“…Recoveries for SPE-LC/MS/MS of pesticides in tap and river water observed a matrix related recovery [40] . In another study, no matrix influence was observed on method recoveries when assessed using deionised water and effluent [41] . This study also analysed influent for steroid levels, though no reference is made to method recoveries obtained using this matrix.…”
Section: Sample Preparationmentioning
confidence: 94%
“…Due to the poor ionization efficiencies of parent estrogens in LC/MS, they have been analyzed by derivatization followed by GC/MS to obtain better detection limits. A common approach in analyzing estrogen metabolites in environmental samples requires conversion of the estrogen metabolites back to the parent compounds through enzymatic hydrolysis [89,90]. Labadie et al [91] highlighted the differences in preparations of the metabolites for GC/MS analysis.…”
Section: Challenges In Metabolite Identification In the Environmentmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20]. These samples are mostly analysed by liquid or gas chromatography coupled with tandem mass spectrometry (LC-MS/MS or GC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…Only 2 papers reported results of stability study in solvent extracts [12,15]. Finally, few papers took into account conjugated estrogens [8,14,19,21], despite the fact that it is essential to measure the total quantity of estrogens including the conjugated fraction to assess accurately the concentrations and fluxes of estrogens in the aquatic environment.…”
Section: Introductionmentioning
confidence: 99%